CREATION OF THE INNOVATIVE ECOSYSTEM AND LIFE QUALITY IMPROVEMENT IN THE REGION - A. Nikonorova (Вестник университета)
The problems of creation of an innovative ecosystem and its impact on the quality of population`s life in the region have considered. The development of innovative ecosystems and formation of innovation centers create prerequisites for the achievement of the technological breakthrough of the country. The complex of factors, affecting the quality of life in the region and the features of the development of innovative infrastructure as a part of the creating ecosystem have analysed in the article. Particular attention in this article has paid to the research of innovative ecosystems as holistic formations, which influence the development of social and economic conditions in the region.